2006
DOI: 10.1007/s00125-006-0401-6
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes impairs progenitor cell mobilisation after hindlimb ischaemia–reperfusion injury in rats

Abstract: Aims/hypothesis A reduction in the number of endothelial progenitor cells (EPCs) is considered a plausible cause of increased cardiovascular risk in diabetes mellitus. The aim of this study was to test the hypothesis that weak bone marrow mobilisation is responsible for the decrease in circulating EPCs in diabetes. Materials and methods We employed a model of hindlimb ischaemia-reperfusion (I/R) injury to study mobilisation of EPCs in control and streptozotocin diabetic rats. EPCs were defined by flow cytometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
213
3
6

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(244 citation statements)
references
References 34 publications
21
213
3
6
Order By: Relevance
“…VEGF-A concentration in human umbilical vein plasma was low but was significantly greater than that in maternal plasma (10.7 Ϯ 4.3 pg/ml vs. 1.3 Ϯ 0.2 pg/ml; p Ͻ .001). The VEGF-A concentration in maternal rat venous blood plasma was consistent with a prior report [40] and was similar in the samples from maternal rat artery. However, VEGF-A was significantly higher in fetal rat plasma The hMSCs spontaneously adhered to fibronectin and laminin, and adhesion was significantly increased as VEGF-A concentration increased (supplemental online Fig.…”
Section: A Maternofetal Vegf-a Concentration Gradientsupporting
confidence: 90%
“…VEGF-A concentration in human umbilical vein plasma was low but was significantly greater than that in maternal plasma (10.7 Ϯ 4.3 pg/ml vs. 1.3 Ϯ 0.2 pg/ml; p Ͻ .001). The VEGF-A concentration in maternal rat venous blood plasma was consistent with a prior report [40] and was similar in the samples from maternal rat artery. However, VEGF-A was significantly higher in fetal rat plasma The hMSCs spontaneously adhered to fibronectin and laminin, and adhesion was significantly increased as VEGF-A concentration increased (supplemental online Fig.…”
Section: A Maternofetal Vegf-a Concentration Gradientsupporting
confidence: 90%
“…In an animal model of hindlimb ischaemia-reperfusion injury, insulin treatment was found to improve the mobilisation of EPCs from bone marrow [45].…”
Section: Discussionmentioning
confidence: 99%
“…We have recently confirmed this hypothesis, showing that bone marrow mobilization of EPCs after ischemia-reperfusion injury is defective in diabetic rats. Inability to mobilize EPCs was associated with downregulation of HIF-1␣ and weakened release of marrowstimulating factors, such as VEGF and SDF-1, ultimately leading to insufficient compensatory angiogenesis (19). Another study has shown that progenitor cell mobilization restored blood flow in diabetic mice (20).…”
Section: Epc Alterations In Diabetesmentioning
confidence: 99%
“…Furthermore, activation of mitogen-activated protein kinases has been revealed as a potential mechanism of EPC dysfunction induced by high glucose (30). A definite demonstration is that correction of hyperglycemia by insulin therapy (19,22) can indeed restore the normal EPC pool.…”
Section: Epc Alterations In Diabetesmentioning
confidence: 99%